Role of sclerostin in mastocytosis bone disease - Aneta Szudy-Szczyrek; Radosław Mlak; Dominika Pigoń-Zając; Witold Krupski; Marcin Mazurek; Aleksandra Tomczak; Karolina Chromik; Aleksandra Górska; Paweł Koźlik; Adrian Juda; Anna Kokoć; Maciej Dubaj; et al. (Scientific Reports)
Abstract Mastocytosis is a heterogeneous group of disorders, characterized by accumulation of clonal mast cells which can infiltrate several organs, most often spine (70%). The pathogenesis of mastocytosis bone disease is poorly understood. The main aim of the study was to investigate whether neoplastic mast cells may be the source of sclerostin and whether there is an association between sclerostin and selected bone remodeling markers with mastocytosis related bone disease. We assessed sclerostin, bioactive sclerostin, and SOST gene expression in HMC-1.2 human mast cell culture supernatants and plasma of SM patients (n = 39). We showed that human mast cells can secrete sclerostin, and after their stimulation with IL-6, there is a significant increase in SOST gene expression. We observed significantly higher levels of sclerostin in patients diagnosed with more advanced disease. We observed a statistically significant correlation between concentations of sclerostin and its bioactive form and the concentration of alkaline phosphatase (ALP), and between sclerostin and interleukin-6 (IL-6). We observed that significantly higher sclerostin concentrations are present in patients with increased sclerosis of the spongy bone. Sclerostin may serve as a marker of more advanced disease and bone disease in mastocytosis. Further studies are justified to evaluate its role in mastocytosis.